Hubungan Religiusitas Dengan Psychological Well-Being Pada Siswa - Hariyani, Aisyah; Sulaiman, Sulaiman (An-Nuha, 2023)
This study aims to determine the relationship between religiosity and psychological well-being in students at SMA Pertiwi 1 Padang. The population in this study was 694 students at SMA Pertiwi 1 Padang. The sampling technique in this study used a simple random sampling technique, namely as many as 65 students. The type of research used is quantitative research with a correlation quantitative research design. Collect data using a questionnaire on two variables, namely psychological well-being as many as 30 items, and religiosity as many as 30 items, then processed and analyzed with statistical tests using Spearman's rank to find a correlation between religiosity and psychological well-being. The result that there is a correlation between religiosity and psychological well-being of SMA Pertiwi 1 Padang students with a correlation coefficient value of r_xy = 0.708 and a significance value of p = 0.000, meaning that the significance of p <0.05 or 0.000 <0.05 the hypothesis in this study can be accepted with a positive level of relationship meaning that the higher the religious attitude, the higher the psychological well-being.